Role of owners of media organizations in the practice of self-censorship - Khattak, Shabeer Ullah; Dr Nasir Iqbal; Dr Abdul Latif; Ibrahim Shareef Dar (Journal of Peace, Development and Communication, 2024)
This study examines the role of owners of media organizations in the practice of self-censorship in Pakistani media. It also explores how the owners’ interference in the affairs of journalists affects their right to expression and strengthens the practice of self-censorship in the media. Most journalists are paid nominal salaries and work on an ad hoc and contractual basis. Their respective media organizations do not even give the majority of journalists permanent appointment letters, and they are purely working on the sweet will of their media organizations. The owners use the media as a tool to safeguard their other businesses, and journalists are forced to protect their business interests. To achieve these objectives, the study employs the quantitative method of survey and the qualitative method of interviews. Data was collected from 366 journalists working in five cities of Pakistan, including Islamabad, Peshawar, Lahore, Karachi, and Quetta. Twenty interviews with journalists, four each from each city, were conducted. For data collection, a simple random sampling of probability sampling method was used. The findings reveal that the interference of the owners has extreme effects on the journalists’ performance, and it is one of the main factors in the practice of self-censorship in Pakistani media.